The resurgence of Lassa fever in Nigeria: economic impact, challenges, and strategic public health interventions - Eneh, Stanley Chinedu; Obi, Chidera Gabriel; Ephraim Ikpongifono, Udokang; Dauda, Zakariya’u; Udoewah, Samson Adiaetok; Anokwuru, Collins Chibueze; Onukansi, Francisca Ogochukwu; Ikhuoria, Ogechi Vinaprisca; Ojo, Temitope Olumuyiwa; Madukaku, Chukwuocha Uchechukwu; Orabueze, Ibuchukwu Nkeonyenasoya; Chizoba, Amara Frances (Frontiers in Public Health, 2025)
Lassa fever remains a persistent public health challenge in Nigeria, with annual outbreaks expanding across the country. Between 2018 and 2023, the disease spread from 20 to 34 of Nigeria’s 37 states, underscoring its endemic nature. Recent data from the Nigeria Centre for Disease Control and Prevention (NCDC) indicates 1,171 suspected cases, 290 confirmed cases, and 53 deaths between January 6 to 26, 2025, with a case fatality rate of 18.3%. Lassa fever transmission is highly seasonal, peaking during the dry months when food scarcity drives rodent-human interactions. Inadequate early detection, weak surveillance systems, and economic constraints exacerbate the burden on Nigeria’s healthcare infrastructure. Environmental, socioeconomic, and systemic healthcare limitations drive the resurgence of Lassa fever. Climate change-induced shifts in temperature and precipitation patterns have disrupted rodent habitats, increasing human exposure to the virus. Additionally, poverty, poor sanitation, and urban expansion facilitate the proliferation of disease-carrying rodents. Limited funding and insufficient healthcare facilities hinder timely responses, contributing to high mortality rates. The economic impact extends beyond healthcare costs to agricultural disruptions, trade restrictions, and workforce productivity losses. To mitigate future outbreaks, Nigeria must adopt a multifaceted strategy that includes robust disease surveillance, the use of environmental data, effective rodent control measures, improved waste management, and strengthened cross-sectoral collaboration and policy implementation. Strengthening healthcare infrastructure, investing in vaccine development will enhance early detection and response efforts. By adopting an integrated One Health approach, Nigeria can improve disease control, reduce fatalities, and alleviate the economic burden of Lassa fever outbreaks.